Biochemical composition of three Opuntia species O. humifusa, O. phaeacantha, O. engelmannii var. lidheimeri. Prospects of their utilization - N. А. Golubkina; N. A. Bagrikova; V. A. Lapchenko; H. V. Lapchenko; T. S. Naumenko; G. D. Levko (Овощи России, 2024)
Relevance. Opuntia distinguished by high adaptability is widespread in many countries of the world. Tolerance to water deficiency and high biological activity provide prospects of its cultivation for food and pharmaceutical industry. In Russia Opuntia is grown in the Crimea, Caucasus, Donbass, Astrakhan region and even in the Central Russia. Evaluation of the Opuntia cultivation efficiency in the Crimea for various utilization supposes the importance of its biochemical characteristics which variability greatly depends on the place of habitat. Materials and Methods. Total antioxidant activity and titratable acidity were determined using titration methods, polyphenol content –using spectrophotometric method, monosaccharide and total sugar concentrations were assessed via reaction with ferricyanide, mucilage levels were determined gravimetrically.Results. Investigation of cladode, inflorescence and fruit biochemical parameters of three Opuntia species: O. humifusa, O. phaeacantha, O. engelmannii, – gathered at the Southern and South-Eastern part of the Crimean peninsular revealed wide variability of fruit mucilage (4.3-16.56% d.w.), sugar and total antioxidant activity. Polyphenol content decreased according to: inflorescence (18.4-21.0) > fruit (11.7-18) > cladodes (10.2-20.0). Fruit monosaccharide content reached (6.2-31) % while in cladodes these values were in the range of 8.1-16.0%. Total sugar content was equal to 32.6-95% in fruit and 15.5-29.7% in cladodes. Concentration of selenium as a natural antioxidant was higher in the cladodes (102-176 µg/kg d.w.) than in fruit (46.8-72 µg/kg d.w.). The highest levels of the total antioxidant activity and titratable acidity were registered in O. engelmannii while the highest sugar, mucilage and taste index were typical for O. humifusa. Nevertheless, O. humifusa was characterized by the lowest fruit mass (6.0-6.3 g) contrary to O. engelmannii (36-40 g). The results suppose prospects of fruit, cladode and inflorescence utilization in food industry, cosmetics and pharmacology with the preference to O. humifusa.